The Disclosure of Sustainability Information in the Local Governments of the Pacific Alliance (2020)
Requests from different categories of users for information on sustainability have manifested the need to disclose non-financial information. The objective of this document is to analyze the level of disclosure of sustainability information from local governments of the Pacific Alliance countries, performing content analysis of the entities’ websites in the year 2018. Results show that local governments of the Pacific Alliance are interested in disclosing sustainability-related information, based on the aspects considered in the Global Reporting Initiative guidelines, but their level of disclosure is low, achieving 40% of the criteria assessed and mainly focused on general and economic information, with lower level of disclosure of social and environmental aspects. This work contributes to the literature on the characteristics of sustainability disclosure in local governments in developing countries such as from the Latin American zone.